(3cJGH eLGH GdOYhIs - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3CMeO Hf eMeO GdedbH HQVi s)
(3ChdgG (B:s
(3Yf CHj gQjQI QVi Gddg Yfg Yf GdfHi Udi Gddg Ydjg hSde bGd (B: ( (3de jJcde ai GdegO EdG KdGKg (B:(3YjSi GHf eQje Ydjg GdSdGe hUGMH LQjL s
(3BNQgG (B:s
(3bGd Gddge Ef cGf UGObkG aCdHSI GdYGajI bGd abGe GdQLd Ydi GdCQV cCf de jcf Hg TF gPG BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdhQb dhfg bGJes
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
Keywords: (3GdJUha hGdBOGH GdTQYjIs